Penggunaan Sari Kacang Tanah dan Pure Buah Kelubi dalam Pembuatan Es Krim - Narulita Adistia Habsari; Shanti Fitriani; Evy Rossi (Universitas Djuanda, 2023)
Ice cream is a frozen food product containing a minimum of 5% fat and 2.5% milk protein, which is obtained by heat-treating and subsequently freezing an emulsion of fat, milk solids and sugar, with or without other substances. This study aimed to obtain the best ratio of peanut juice and kelubi puree in making ice cream that meet the quality of SNI 01‒3713‒1995. The study was conducted using a completely randomized design (CRD) with four treatments and four replications. Data were analyzed using analysis of variance (ANOVA) and then continued with Duncan’s Multiple Range Test (DMRT) at 5% level. The result showed that the ratio of peanut juice and kelubi puree significantly affected fat, protein, total solids, overrun, viscosity, melting time, and descriptive and hedonic sensory tests. The ratio of peanut juice and kelubi puree (92.5:7.5) was chosen as the best treatment, which had 5.62% fat, 5.83% protein, 144.03 ppm antioxidant activity, 35.44% total solids, 2950.85 cP viscosity, 43.16% overrun, and 13.26 minutes melting time with a description of ivory white color, peanut’s flavor, soft, and a little peanut taste. Panelists liked the hedonic assessment of color, aroma, softness, taste, and overall assessment. Keywords: ice cream, kelubi puree, peanut juice